Analisis Pemanfaatan Penerima Program Keluarga Harapan (PKH) di Lembang Sereale - Fani Datu Arung; Dina Ramba; Yohanis L. Ta’dung (Universitas Katolik Widya Karya Malang, 2023)
The aim of this research is to determine the analysis of the utilization of assistance for recipients of the Family Hope Program (PKH) in Lembang Sereale. This research uses qualitative methods. Qualitative methods are research procedures that produce descriptive data in the form of written or spoken words from people or actors who can be observed. Data collection procedures for observations were carried out using several methods, namely observation, interviews and documentation. The results that the researchers obtained were that some of the PKH beneficiaries were classified as economically well off, so this resulted in the assistance they received not being on target. This can be seen from the place of residence and economic conditions that can be categorized as decent. The construction of the houses used is also permanent, the lighting for PKH recipient houses uses electricity and gas is used for daily cooking. However, this inaccurate target is not entirely the fault of the community or local village officials, because at the time of the nomination of potential PKH beneficiaries they were still relatively poor, the time span for receiving aid was relatively long so the community had experienced economic development.